Autumn de-worming. (2nd November 2021) - Rendle, David
Abstract : Autumn is traditionally a time when most horses are de-wormed with one or more products that are effective against tapeworms and both adult and larval roundworms. However, the increasing prevalence of resistance and availability of diagnostics should prompt scrutiny of whether blanket de-worming at this time of year is appropriate. If management is good and horses are at low-risk of clinical disease, then there may be no need to use anthelmintics. Serology provides a means of assessing exposure to both cyathostomins and tapeworms, but it has its limitations and does not provide a validated means of assessing the risk of parasitic disease. The results of serology, results of faecal worm egg counts performed in the population through the preceding grazing season, and knowledge of management practices in the population should all be considered when assessing whether the risk of the disease to the individual is such that it must take priority over the ever-increasing threat of resistance in the equine population.